Revitalise your knowledge thru’ clinical data interpretation - Hambali, Zarida; Samsudin, Intan Nureslyna; Thambiah, Subashini C. (Universiti Putra Malaysia Press, 2013)
Revitalize your knowledge thru’ Clinical Data Interpretation is an overview and revision guide for medical students, postgraduate students, house-officers, general practitioners, nurses and health scientists. This book is written to highlight the importance of correlating clinical presentations (symptoms and signs), physical findings and laboratory investigations in making diagnosis and managing health of patients. The questions are designed to help readers think critically on the pathophysiology of various clinical disorders and the biochemical changes that may occur based on the results of the laboratory investigations. This book is recommended for undergraduate medical students. However, it is of significant benefit to trainee medical lecturers and junior medical officers, candidates of biomedical and other related health sciences.